Sexual Health and Sexually Transmitted Infections in the North American Arctic - Law, Dionne Gesink (Centers for Disease Control and Prevention, 2008)
Our objective was to describe the basic epidemiology of sexually transmitted infections for Arctic and sub-Arctic regions of North America. We summarized published and unpublished rates of chlamydial infection and gonorrhea reported from 2003 through 2006 for Alaska, Canada, and Greenland. In 2006, Alaska reported high rates of chlamydial infection (715 cases/100,000 population) compared with the United States as a whole; northern Canada reported high rates of chlamydial infection (1,693 cases/100,000) and gonorrhea (247 cases/100,000) compared with southern Canada; and Greenland consistently reported the highest rates of chlamydial infection (5,543 cases/100,000) and gonorrhea (1,738 cases/100,000) in the Arctic. Rates were high for both men and women, although the highest incidence of infection was predominantly reported for young women in their early twenties. We propose that community-based participatory research is an appropriate approach to improve sexual health in Arctic communities.